INVESTIGATING THE RELATIONSHIP BETWEEN ENGLISH LANGUAGE PROFICIENCY AND PROGRAMMING SKILLS IN COMPUTER ENGINEERING EDUCATION - Lika Silvia Batubara (INJOSEDU: International Journal of Social and Education, 2025)
This research investigates the intricate relationship between English language proficiency and programming skills within the domain of computer engineering education. In an increasingly globalized world, where English serves as a lingua franca in the field of technology, the correlation between language competence and technical aptitude becomes pivotal. This study employs a mixed-methods approach, encompassing both quantitative and qualitative analyses, to comprehensively explore this relationship. Quantitative data are collected through standardized English language proficiency tests and programming assessments, while qualitative insights are derived from interviews and surveys among computer engineering students. The findings shed light on the nuanced interplay between English language proficiency and programming skills, uncovering potential implications for curriculum design, pedagogical strategies, and student support services in computer engineering education. By elucidating the dynamics of this relationship, this research aims to inform educators, policymakers, and stakeholders in optimizing educational practices to better equip computer engineering students for success in the global technological landscape.